Synergistic interface between metal Cu nanoparticles and CoO for highly efficient hydrogen production from ammonia borane. Issue 17 (13th April 2023) - Li, Hongmei; He, Wenxue; Xu, Liuxin; Pan, Ya; Xu, Ruichao; Sun, Zhihu; Wei, Shiqiang
Abstract : TiO2 -supported Cu x –(CoO)1− x /TiO2 catalysts exhibit high catalytic efficiency for NH3 BH3 hydrolysis. The Cu–CoO interface provides bifunctional synergistic sites for H2 generation, with activation and adsorption of NH3 BH3 and H2 O on the surface of Cu and CoO, respectively. Abstract : The development of efficient non-noble metal catalysts for the dehydrogenation of hydrogen (H2 ) storage materials is highly desirable to enable the global production and storage of H2 energy. In this study, Cu x –(CoO)1− x /TiO2 catalysts with a Cu–CoO interface supported on TiO2 are shown to exhibit high catalytic efficiency for ammonia borane (NH3 BH3 ) hydrolysis to generate H2 . The best catalytic activity was observed for a catalyst with a Cu : Co molar ratio of 1 : 1. The highest dehydrogenation turnover frequency (TOF) of 104.0 molH2 molmetal −1 min −1 was observed in 0.2 M NaOH at room temperature, surpassing most of the TOFs reported for non-noble catalysts for NH3 BH3 hydrolysis. Detailed characterisation of the catalysts revealed electronic interactions at the Cu–CoO heterostructured interface of the catalysts. This interface provides bifunctional synergetic sites for H2 generation, where activation and adsorption of NH3 BH3 and H2 O are accelerated on the surface of Cu and CoO, respectively. This study details an effective method of rationally designing non-noble metal catalysts for H2 generation via a metal and transition-metal oxide interface.